1)
îl înlocuim pe x cu -1
a)
[tex]3 \times ( - 1) - 7 = 10 \\ - 3 - 7 = 10 \\ - 10 = 10fals[/tex]
b)
[tex]2 \times ( - 1) = - 4 \\ - 2 = - 4fals[/tex]
c)
[tex] \frac{2 + ( - 1)}{6} = \frac{2 \times (- 1) - 1}{3} \\ \frac{1}{6} = \frac{ - 2 - 1}{3} \\ \frac{1}{6} = \frac{ - 3}{3} \\ \frac{1}{6} = - 1\\ fals[/tex]
2)
a)
[tex]17 + x = - 3 \\ x = - 3 - 17 \\ x = - 20[/tex]
b)
[tex]3 - x = 5 \\ - 3 = 5 - 3 \\ - x = 2 | \times ( - 1) \\ x = - 2[/tex]
c)
[tex]x \div (- 8) = 7 \\ x = 7 \times (- 8) \\ x = - 56[/tex]
…ᘛ⁐̤ᕐᐷฅ^•ﻌ•^ฅ